Reflections on the Science and Indigenous Knowledge Systems Project: Voices of the Participants - Nhalevilo, Emilia Afonso; Ogunniyi, Meshach (South African Journal of Higher Education, 2016)
The Science and Indigenous Knowledge Systems Project (SIKSP), located in an African University, has since its inception in 2004 been training pre-service and practising teachers how to implement an inclusive science-Indigenous Knowledge (IK) curriculum which calls on teachers to integrate IK with science in their classrooms. This paper, based on an interview, presents some of the participants’ reflections, voices, sentiments and feelings about SIKSP. The findings show that the project helped to raise the participants’ awareness about IK, and its relevance to contemporary life. The findings foresee some of the challenges involved in the implementation of the new curriculum in terms of: the multiple representations of IK; the potential conflict that might arise at the inter-section of science and IK; the complexity of a multicultural classroom; teachers’ willingness and/or ability to adopt a new role in the classroom than the status quo; and the paucity of instructional strategies compatible with the goals of the new curriculum. Regardless of all these factors, participants felt emancipated to teach IK and they expressed the need for administrative support and follow-ups workshops . They also suggested that in order to make a difference in the country the project should be expanded to other schools and provinces.